Familial context influences media usage in 0- to 4-year old children - Paulus, Frank W.; Joas, Jens; Friedmann, Anna; Fuschlberger, Tamara; Möhler, Eva; Mall, Volker (Frontiers in Public Health, 2024)
Background The use of digital media (e.g., smartphones, tablets, etc.) and the Internet have become omnipresent for every age group and are part of children’s and parents’ everyday life. Focusing on young children, the availability of media devices, their use as well as associated problems (e.g., in social, emotional and motor development) have increased in recent years. Of particular interest for prevention of these problems in early childhood is the relationship between the familial context (parental digital media use, Problematic Internet Use, school graduation, presence of siblings) and the digital media use of infants and toddlers. The present study’s goal was to describe media usage in 0–4-year-old children and to identify the potential relationship between familial context factors and child media usage. Methods The sample included N = 3,035 children aged 0 to 3;11 years (M = 17.37 months, SD = 13.68; 49.13% female). Recruitment took place within the framework of a restandardization study for a German developmental test. The parents of the participants answered a questionnaire on socio-demographics, on child media use, and on parental media use. Questions on parental media use included the full version of the Short Compulsive Internet Use Scale (S-CIUS). Results Significant increases in media usage times with child age were identified, but no significant gender differences. A multiple regression analysis revealed that increasing maternal total media usage time, a higher parental S-CIUS score, lower school leaving certificate of both mother and father, and increasing child’s age led to higher child media usage time. Having siblings diminished young children’s media usage in this study. Having more than one child and having children aged over a year was associated with a higher parental S-CIUS score. Conclusion Family factors such as maternal media use time, Problematic Internet Use and lower school graduation are significantly associated with young children’s digital media use. Parents should be aware of their personal influence on their children’s media use which might be due their role in terms of model learning.